Effect of urbanization on livelihood patterns of the farm households in the peri-urban area of Bengaluru - Ravi, K N; Ponnusamy, Kuppusamy (Indian Journal of Dairy Science, 2016)
Rapid growth of urbanization has a cascading effect on the land use pattern and consequently the livelihood pattern of peri-urban farming communities. Farmers who sold their precious farm land to real estate agencies in a pre mature decisive way faces number of difficult situations, seriously affecting their livelihoods in the peri-urban areas. A study was conducted with 160 farmers in the peri-urban area of Bengaluru to ascertain the household livelihood strategies among the partially farm land sold farmers (PFSF) and another completely farm land retained farmers (CFRF). Focus group discussion was employed to understand the reasons for change in their livelihood options and selling of the farm land. Crop+dairy (26.3%) was major the combination in the peri-urban area of Bengaluru followed by crop+dairy+allied non-agriculture activity (20.6%) and allied non-agriculture activities (15%). Most of the households added new livelihood occupation from off-farm activities and only few were added the dairy and crop production. About 9.4 per cent of total respondents left agriculture labour which might have led to scarcity of labour for farm activities in peri-urban area of Bengaluru. The findings of the study recommend to make feasible and viable policies to facilitate a balanced improvement for agriculture and non agriculture by understanding gist of peri-urban dynamics.